12(-82x+26)=84(2x+62)

Simple and best practice solution for 12(-82x+26)=84(2x+62) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(-82x+26)=84(2x+62) equation:


Simplifying
12(-82x + 26) = 84(2x + 62)

Reorder the terms:
12(26 + -82x) = 84(2x + 62)
(26 * 12 + -82x * 12) = 84(2x + 62)
(312 + -984x) = 84(2x + 62)

Reorder the terms:
312 + -984x = 84(62 + 2x)
312 + -984x = (62 * 84 + 2x * 84)
312 + -984x = (5208 + 168x)

Solving
312 + -984x = 5208 + 168x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-168x' to each side of the equation.
312 + -984x + -168x = 5208 + 168x + -168x

Combine like terms: -984x + -168x = -1152x
312 + -1152x = 5208 + 168x + -168x

Combine like terms: 168x + -168x = 0
312 + -1152x = 5208 + 0
312 + -1152x = 5208

Add '-312' to each side of the equation.
312 + -312 + -1152x = 5208 + -312

Combine like terms: 312 + -312 = 0
0 + -1152x = 5208 + -312
-1152x = 5208 + -312

Combine like terms: 5208 + -312 = 4896
-1152x = 4896

Divide each side by '-1152'.
x = -4.25

Simplifying
x = -4.25

See similar equations:

| 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 | | 2n(8n+1)=0 | | 9x+90+y=180 | | x(-5x+2)=24 | | -3u-w=u+7w | | 4x+8+5x-7=180 | | 12+6x=42 | | 6=t+7s | | 6(t-3)+6t=4(3t+5)-12 | | 5x-9x+8=-2+6 | | -2+3x=12 | | -6z-6=-12z+12 | | 9x-6+6x-1+82=180 | | ((-2w^2)/(v^4))^3 | | 5(-2)-2x=20 | | 1/40*n=60 | | 8x^2+21x-28=0 | | 5y+4x=20 | | 1/40*x100=60 | | 2/10x=10 | | x+2=x^2+3x-4 | | x-8.3=-4.5 | | x+2=x^2+2x-4 | | 4x^6-4x^5-8x^4-9x^2+9x+18=0 | | p+37=15 | | 4n+7n=20 | | 2*n=327 | | 0=-1/2x+4 | | (2w-1)2=4(w-3)2 |

Equations solver categories